DAMPAK LARANGAN PUKAT HARIMAU PADA KEHIDUPAN BURUH NELAYAN (Studi Kasus di Kelurahan Aek Muara Pinang Kecamatan Sibolga Selatan Kota Madya Sibolga) - Tampubolon, Hasiholan; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Tiger trawlers have long been banned by the Government but are still used by fishermen today. Tiger trawlers are considered to damage the marine ecosystem because of fishing gear that can damage coral reefs and the generation of fish and other marine ecosystems. Because fishermen, especially in the Sibolga City area, have long used tiger trawlers, so that until now the fishermen are still using it even though it has been banned in law. It is indeed very difficult to change the condition of current trawlers, but it is already a firm Government policy to ban trawlers now to operate again and fishermen especially fishermen who have tiger trawlers in Sibolga City currently must find alternative fishing gear to looking for and getting fish in the sea .. Formulation of the problem from this research, 1. What are the impacts on the fishermen after the demolition of trawlers? 2. What are the social and economic changes of fishermen after the demolition of trawlers? The type of this research is descriptive qualitative research, the research subject who became the informant in this study as many as seven people who were previously trawler fishermen, of which three fishermen who had long been trawlers and four were new fishermen working as trawlers. The technique of taking the subject of the research was done by snow ball sampling technique. Particularly the fishing community of Aek Muara Pinang Village must have experienced the positive and negative effects of trawling. Keywords : Tiger Trawlers, Fishermen, Aek Muara Pinang Village